Towards prevalence of Negeri Sembilan Malay traditional architecture for future communities: misconceptions / Mawar Masri. - Masri, Mawar (Universiti Teknologi MARA Cawangan Selangor, 2018)
Abstract Negeri Sembilan’s unique identity is facing gradual disappearance endangering future generation’s identity’s ownership as well as cultural and built environment quality due to such misconception. This paper seek to present the findings of a comprehensive literature reviews which then tested by a perception survey. The literature review is part of the research activities aimed in unravelling the authenticity of Negeri Sembilan traditional houses. The research methodology was qualitative. This paper enables understanding of apparent misconception and an important milestone on an ongoing research towards preserving the Negeri Sembilan architectural identity for our future communities in facing environmental challenges.